Bacterial cellulose and silk fibroin biopolymers: biotemplates to design nanostructured materials for optical applications - Santos, Molíria Vieira dos [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Among all natural polymers, bacterial cellulose and silk fibroin offer unlimited opportunities for processing, functionalization, and biological integration. This thesis presents the preparation and characterization of nanostructured materials based on bacterial cellulose produced by Gluconacetobacter xylinus bacteria, as well as regenerated silk fibroin stemmed from the cocoons of silkworms (Bombyx mori) for optical applications. Firstly, dried bacterial cellulose membranes were utilized to prepare cellulose nanocrystals (CNC). CNC were casted in the form of thick iridescent films whose color originates in the periodic patterning of layers in a chiral nematic texture created by self-assembly of rod crystallites. Once the CNC films were obtained, self-sustainable films were coated with a low molecular weight nematic liquid crystal (LC), 4′-(hexyloxy)-4-biphenylcarbonitrile (HOBC). The materials were obtained as free-standing iridescent films, with chiral nematic structure that exhibited modulated optical properties, in response to external stimulus, such as thermal gradient or relatively small electrical voltage. The scanning electron microscopy (SEM) confirmed that the composite film structure comprises the multi-domain Bragg reflectors. The relationship between the surface structure and thermo-responsive properties of investigated HOBC coated with CNC film was examined using transmission optical microscopy (TOM). Additionally, electrostatic force microscopy (EFM) measurement was employed to prove the effect of external stimuli, in this case applied voltage, on the HOBC liquid crystal coated with CNC film. The second part of this thesis involves the design of luminescent iridescent films through the combination of CNC suspension with tetraethoxysilane (TEOS) and ethanolic solutions of Rhodamine 6G (Rh6G). These materials were obtained as freestanding composite films with chiral nematic organization. The optical properties of such films can be tuned through changes in the silica/CNC proportion during the preparations. Photoluminescence measurements, as function of the detection angle, were realized in order to investigate the influence of photonic structure in the light emission of composite films. Our findings demonstrated that the photonic structure of the film acts as an inner- filter, causing selective suppression of the light emitted with a variation of the detection angle. This behavior was found to be dependent of the bandgap position on the photonic structure of these materials. Lastly, we designed structured organic-inorganic hybrids (OIH) based on silica and silk fibroin. The materials were obtained as robust monoliths possessing different fibroin fractions. The SEM images demonstrated in-situ self-assembly of fibroin nanofibers dispersed into the IOH monoliths. Structural characterization of OIH monoliths was performed by Raman and solid state NMR spectroscopies. Our findings demonstrated that precipitated fibroin presented prevailing β-sheet conformation. Furthermore, we demonstrated that the fibroin nanofibers can be used as biotemplates, acting as a sacrificial material to development porous silica monoliths. The porous silica monoliths doped with rhodamine 6g (Rh6G) exhibited efﬁcient RL action with low threshold power excitation and narrowing linewidth. From the spectral behavior, it is inferred that the RL operates in the diffusive regime in hierarchical macro–mesoporous network. In addition, analysis of the emission spectra showed two gain mechanisms coupled, specifically the random lasing and the stimulated Raman scattering, which suggest that designed materials can also be promising for random Raman laser applications.

Entre os polímeros naturais, celulose bacteriana e fibroína da seda oferecem inúmeras oportunidades para funcionalização, processamento e integração biológica. Esta tese apresenta a preparação e caracterização de novos materiais nanoestruturados para aplicações ópticas utilizando celulose bacteriana produzida pela bactéria Gluconacetobacter xylinus, como também em fibroína regenerada extraída de casulos do bicho da seda (Bombyx mori). Primeiramente, membranas de celulose bacteriana secas foram utilizadas para a preparação de nanocristais de celulose (NCC). Os nanocristais de celulose foram processados na forma de filmes espessos e iridescentes nos quais a cor tem origem de padrões periódicos de camadas em uma estrutura nemática quiral criada pelo alto montagem dos bastões cristalinos. Uma vez obtido o filme de NCC, o mesmo foi revestido com um cristal líquido nemático de baixo peso molecular, 4’- (hexiloxi) - 4 - bifenilcarbonitrila (HOBC). O material foi obtido como um filme auto-suportado, iridescente, formado por uma estrutura nematic quiral e que exibe moduladas propriedades em resposta a estímulos externos, tais como, gradiente de temperatura e relativa pequena voltagem elétrica. Imagens de microscopia eletrônica de varredura (MEV) confirmaram a estrutura do filme formada por múltiplos domínios refletores de Bragg. A relação entre a estrutura da superfície e as propriedades de resposta térmica do revestimento de HOBC no filme foram investigadas utilizando microscopia óptica de transmissão (TOM). Além disso, medidas de microscopia de força eletrostática foram empregadas para provas o efeito do estímulo externo, neste caso da voltagem aplicada, no revestimento de cristal líquido HOBC no filme. A segunda parte desta tese envolve a preparação de filmes iridescente luminescentes através da combinação da suspensão de NCC com tetraetoxisilano (TEOS) e uma solução etanólica de rodamina 6G (Rh6G). Estes materiais foram obtidos como filmes compósitos auto suportados com ordenação nemática quiral. As propriedades ópticas dos filmes foram sintonizadas através de mudanças na proporção de sílica/NCC na preparação. Medidas de fotoluminescência em função do ângulo foram realizadas a fim de investigar a influência da estrutura fotônica com ordenação nemática quiral na emissão de luz pelos filmes compósitos. Os resultados demonstraram que a estrutura fotônica dos filmes atuam como um filtro interno causando supressão seletiva da luz emitida com a variação do ângulo de detecção. Este comportamento mostrou-se dependente da posição da banda proibida destes materiais. Por fim, nós preparamos híbridos orgânico - inorgânicos (HOI) baseados em sílica e fibroína da seda. Os materiais foram obtidos em forma de monolitos robustos contendo diferentes concentrações de fibroína. As imagens de MEV apresentam a precipitação de nanofibras de fibroína dispersas dentro dos HOIs. A caracterização estrutural das amostras foi realizada por espectroscopia Raman e ressonância magnética nuclear (RMN) do estado sólido. Os resultados demonstraram que a fibroína precipitada apresenta preferencial conformação folha- β. Nós demonstramos ainda que as nanofibras de fibroína podem ser utilizadas como moldes, atuando com um material de sacrifício para a produção de monolitos de sílica porosos. Os monolitos de sílica porosa dopados com rodamina 6G (Rh6G) exibiram eficiente ação laser aleatório (LA), com baixo limiar laser e estreita largura de banda. A partir do comportamento espectral, infere-se que o LA opera no regime difusivo na rede hierarquia formada por macro e mesoporos. Além deste comportamento, através de análise do espectro de emissão foi observado o acoplamento de dois mecanismos, laser aleatório e espalhamento Raman estimulado, o que sugere que o material obtido também pode ser promissor para aplicações em laser aleatório Raman.
Biopolímeros de celulose bacteriana e fibroína da seda: biotemplates para a preparação de materiais nanoestruturados para aplicações ópticas
Keywords: Bacterial cellulose; Silk fibroin; Cellulose nanocrystals; Nematic liquid crystal; Silica; Organic-inorganic hybrids; Photonic devices and random lasers; Celulose bacteriana; Fibroína da seda; Nanocristais de celulose; Sílica; Híbridos orgânicos-inorgânicos; Dispositivos fotônicos e lasers aleatórios